LEARNING LISTENING BY USING LYRICSTRAINING: STUDENTS' PERCEPTION - Ulul Azmi, Danang; Anjarwati, Rosi (Universitas Islam Lamongan, 2024)
The rapid development of technology in teaching English listening has brought a new perspective both from the teacher and students. This research aimed to discover students' perception toward learning listening by using lyricstraining, an online web providing sound and song lyrics with various features. This research was a survey that was applied to a group of students who have experienced learning listening by using Lyricstraining. The study was carried out on tenth-grade students attending a senior high school in Jombang, with 40 students as the respondents. A close-ended- questionnaire in four poins Likert Scale (Stongly Disagree, Disagree, Agree, and Strongly Agree) was used to collect the data. Analyzing by using percentages, it was obtained that students' perception toward using Lyricstraining gain a positive result. This is evident from the trend of the average score of students' responses, which indicates an achievement of 89% agreement and strong agreement.